Genes with Restricted Introgression in a Field Cricket (Gryllus firmus/Gryllus pennsylvanicus) Hybrid Zone Are Concentrated on the X Chromosome and a Single Autosome. Issue 11 (1st November 2015) - Maroja, Luana S; Larson, Erica L; Bogdanowicz, Steven M; Harrison, Richard G
Abstract: Characterizing the extent of genomic differentiation between recently diverged lineages provides an important context for understanding the early stages of speciation. When such lineages form discrete hybrid zones, patterns of differential introgression allow direct estimates of which genome regions are likely involved in speciation and local adaptation. Here we use a backcross experimental design to construct a genetic linkage map for the field crickets Gryllus firmus and Gryllus pennsylvanicus, which interact in a well-characterized hybrid zone in eastern North America. We demonstrate that loci with major allele frequency differences between allopatric populations are not randomly distributed across the genome. Instead, most are either X-linked or map to a few small autosomal regions. Furthermore, the subset of those highly differentiated markers that exhibit restricted introgression across the cricket hybrid zone are also concentrated on the X chromosome (39 of 50 loci) and in a single 7-cM region of one autosome. Although the accumulation on the sex chromosome of genes responsible for postzygotic barriers is a well-known phenomenon, less attention has been given to the genomic distribution of genes responsible for prezygotic barriers. We discuss the implications of our results for speciation, both in the context of the role of sex chromosomes and also with respect to the likely causes of heterogeneous genomic divergence. Although we do not yet have direct evidence for the accumulation of ecological, behavioral, or fertilization prezygotic barrier genes on the X chromosome, faster-X evolution could make these barriers more likely to be X-linked.